2020
DOI: 10.3390/ijerph17197002
|View full text |Cite
|
Sign up to set email alerts
|

Partnership Status and Living Situation in Persons Experiencing Physical Disability in 22 Countries: Are There Patterns According to Individual and Country-Level Characteristics?

Abstract: Persons experiencing disabilities often face difficulties to establish and maintain intimate partnerships and the decision whether to live alone or with others is often not their own to make. This study investigates whether individual and country-level characteristics predict the partnership status and the living situation of persons with spinal cord injury (SCI) from 22 countries. We used data from 12,591 participants of the International SCI Community Survey (InSCI) and regressed partnership status and livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…One potential explanation is that formal help is less available in countries with lower SED and that informal care from family, friends and within neighborhoods is comparably higher [66], leading to higher relationship satisfaction. Earlier findings from the InSCI study also showed that persons from higher SED countries more often live alone [67]. This may not only affect their relationship satisfaction as everyday social interaction with persons in the same household is missing, but could also affect their social participation outside the home as household members could be instrumental in overcoming environmental barriers.…”
Section: Main Effectsmentioning
confidence: 91%
“…One potential explanation is that formal help is less available in countries with lower SED and that informal care from family, friends and within neighborhoods is comparably higher [66], leading to higher relationship satisfaction. Earlier findings from the InSCI study also showed that persons from higher SED countries more often live alone [67]. This may not only affect their relationship satisfaction as everyday social interaction with persons in the same household is missing, but could also affect their social participation outside the home as household members could be instrumental in overcoming environmental barriers.…”
Section: Main Effectsmentioning
confidence: 91%
“…In consideration of injury surveillance in the context of SCI/D, an important concept in interpreting the epidemiological literature is that differences in the lived experience within or between countries can impart significant differences in prevalence and influence survival, co-morbidity profiles, and the outcomes of survivors [ 6 9 ]. At an individual level these differences may or may not involve relationships between demographic, personal, ethno-cultural or socio-economic factors and prevalence or between these factors and the lived experience [ 6 9 ]. At the contextual level numerous reports have confirmed that personal , and functional factors, related health conditions, quality of life [ 9 ], environmental barriers [ 8 ] and socio-economic [ 10 ] status may influence the lived experience [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…At an individual level these differences may or may not involve relationships between demographic, personal, ethno-cultural or socio-economic factors and prevalence or between these factors and the lived experience [ 6 9 ]. At the contextual level numerous reports have confirmed that personal , and functional factors, related health conditions, quality of life [ 9 ], environmental barriers [ 8 ] and socio-economic [ 10 ] status may influence the lived experience [ 11 , 12 ]. Another level of complexity involves the influence of health system performance on these contextual factors and central to this is the interaction between this variable and the quality of public health data repositories or registries.…”
Section: Introductionmentioning
confidence: 99%